Circles, PSHE and Citizenship : Assessing the Value of Circle Time in Secondary School. - Tew, Marilyn (Lucky Duck Books., 2007)
The circle time teaching strategy is used extensively and successfully in primary schools, but secondary settings often find it difficult to implement. In this book, the authors advise on how a circle time programme can be developed in secondary schools, involving both staff and students. Drawing on their experience of using circle time to deliver the PSHE and Citizenship curricula, they present a framework that that can be followed or adapted by other secondary schools. The development includes: - consultation with students - choosing the topics for the programme of study - lesson plans writt.